2019
DOI: 10.2337/db19-308-lb
|View full text |Cite
|
Sign up to set email alerts
|

308-LB: A Short Period of Exposure to Air Pollution (PM2.5) Is Sufficient to Induce Dysbiosis, Hyperphagia, and Fat Mass Gain

Abstract: Fine particulate matter (PM2.5) is the most harmful component of air pollution and is associated with an increased risk of cardiometabolic diseases, such as T2DM. The small diameter of PM2.5 allows it to be inhaled and subsequently invades tissues through the airways. Intake of PM2.5 is also possible even if this is not the primary route of entry of PM2.5 into the body. However, it is still unclear whether ingestion and inhalation of PM2.5 in a short time would be sufficient to alter the gut microbiota and ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Overconsumption of calorie-dense food and lack of physical activity were traditionally accepted as the root cause of obesity. Recently, accumulating studies indicated that environmental pollutant exposure during curial stages, such as pregnant period may predispose the offspring of exposed individuals to alter body weight as well as lipid hemostasis, irrespective of diet and exercise [44,45]. However, whether maternal exposure to PSNPs affect the development of obesity has not bees systemically investigated and the underlying mechanism remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Overconsumption of calorie-dense food and lack of physical activity were traditionally accepted as the root cause of obesity. Recently, accumulating studies indicated that environmental pollutant exposure during curial stages, such as pregnant period may predispose the offspring of exposed individuals to alter body weight as well as lipid hemostasis, irrespective of diet and exercise [44,45]. However, whether maternal exposure to PSNPs affect the development of obesity has not bees systemically investigated and the underlying mechanism remain unclear.…”
Section: Discussionmentioning
confidence: 99%